AN ANALYSIS OF PROJECT BASED LEARNING METHOD IN INTERPERSONAL INTELLIGENCES OF PRESCHOOL CHILDREN - Eka Mei Ratnasari (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2020)
This study aims to determine the effect of project-based learning methods on the development of the interpersonal intelligence of preschool children. Subjects in this study were preschool children especially 4-5 years old. The subject consisted of two kindergartens in Yogyakarta Indonesia, the participants consisted of 31 children. Thus, the data were used as a quasi-experimental research design. The experimental group was taught with a project-based learning method while in the control group with conventional methods. The data collection was an observation sheet. The research data obtained were analyzed using the t-test in the SPSS.16 program to see the differences between the experimental group and the control group. The results showed that there is a significant influence of project-based learning methods toward the interpersonal intelligence of preschool children. The recommendation was provided to parents, academics, practitioners in the discussion that especially emphasized addressing the need to increase opportunities for the interpersonal intelligence of preschool children in good stimulation.